Metabolic diversity in sweet potato (Ipomoea batatas, Lam.) leaves and storage roots - Drapal, Margit; Rossel, G.; Heider, B.; Fraser, Paul D. (Oxford University Press, 2019)
Sweet potato (Ipomoea batatas, Lam.) is an important root vegetable in developing countries. After its domestication in Neotropical America, human migration led to the distribution of the sweet potato plant throughout the world. Both leaf and storage root are high in compounds of nutritional value. Yet, the storage roots are of particular value due to their significant content of provitamin A (β-carotene). The breeding effort for elite sweet potato lines led to the reduction of genetic diversity and the potential to improve other traits. The focus of the present study was to assess the metabolic diversity of 27 sweet potato cultivars including landraces and improved varieties. A metabolite profiling approach was optimised for sweet potato leaf and storage root tissue and 130 metabolites identified with three different analysis platforms. The data highlighted a lack of correlation between storage root phenotype and leaf metabolism. Furthermore, the metabolic diversity of storage roots was based on the secondary metabolism, including phenylpropanoids and carotenoids. Three cultivars of three different flesh colouration (yellow, orange and purple) showed a significant difference of the primary metabolism. This data demonstrates the value of metabolite profiling to breeding programs as a means of identifying differences in phenotypes/chemotypes and characterising parental material for future pre-breeding resources.